Effect of silver nanoparticles on sterilization of different explant sources of Gerbera jamesonii cultured in vitro - Hien, Vu Thi; Tung, Hoang Thanh; Khai, Hoang Dac; Luan, Vu Quoc; Cuong, Do Manh; Lich, Tran Van; The Vinh, Bui Van; Thi Huong, Trinh; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2021)
In this study, silver nanoparticles effects on the sterilization of different sources of explants (young leaves, young flower stalks and young flower buds) of Gerbera as well as on the in vitro morphogenesis and their growth were investigated. The explants were sterilized and cut transversally (1 mm) with the flower stalk, square (0.5 × 0.5 cm) for the leaf sample, longitudinally (0.5 mm) for the flowers (removed the petals) and cultured on MS medium; then, the explants (contamination-free or no browning/necrosis) were transferred into MS medium supplemented with 0.02 mg/L TDZ plus 0.8 mg/L adenine, 10% coconut water, 30 g/L sucrose and 8 g/L agar in 15 days. The results showed that AgNPs at the appropriate concentration and duration treatment was effective in explant sterilization of flower bud (0.02% AgNPs and 20 min), flower stalks (0.02% AgNPs and 30 min) and young leaves (0.05% AgNPs and 20 min) after 15 days of culture. In addition, 3 types of morphogenesis including callus induction, somatic embryogenesis and direct shoot regeneration of explants derived from sterilization by AgNPs were improved as compared to that of HgCl2. In addition, research on the optimal medium for shoot multiplication, rooting as well as evaluation of acclimatization and the growth at the greenhouse were also studied. Results showed that MS medium supplemented with 2 mg/L NAA combined with 0.5 mg/L BA and 2 mg/L KIN is suitable for shoot multiplication; meanwhile, MS medium supplemented with 2 mg/L NAA improved rooting ability as well as quality of plantlets and to improving survival rate and acclimatization of Gerbera cultured in vitro.